Influence of technical parameters on performance in discus throwing - Liu, H.; Leigh, S.; Yu, B. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. I, 2008)
Introduction: The discus throwing event is the most technically and physically demanding throwing event in track and field. The demands of this event are as they are because discus throwing has to be performed at a high speed in a limited space. Current literature contains little scientific information regarding the biomechanics of discus throwing. The purpose of this study was to determine the effects of selected technical factors on the performance of the discus throw using multiple regression analyses. Methods One hundred and thirty legal trials of elite male discus throwers and 160 legal trials of elite female discus throwers competing in international and USA Track & Field National Championships from 1990 to 2006 were included in this study. Athletes` performances in these trials were recorded using two SVHS video camcorders at a frame rate of 60 frames/sec for Direct Linear Transformation procedure. The real-life 3-D coordinates of 21 body landmarks and the center of the discus were estimated using the Direct Linear Transformation procedure. Six critical events during discus throwing were identified as maximum backswing, right foot off, left foot off, right foot down, left foot down and release. The hip-shoulder and shoulder-arm separation angles, trunk tilt angle, and throwing-arm elevation angle were reduced at each of these critical instants for each trial. Discus release speed, the angle and height of release, the horizontal and vertical discus release velocity, and the changes in speed during five phases were also reduced. Multiple regression analyses were performed to determine the effects of hip-shoulder and shoulder-arm separations, trunk tilt angles, and throwing-arm elevation angles on the release speed and changes in discus speed during the delivery phase for male and female athletes separately. A backward selection procedure was used to determine the best regression equation in each analysis. A Type I Error rate of 0.05 was chosen to indicate statistical significance. Results The gain of discus speed during the delivery phase had significant effect on the official distance of the discus throwing. Shoulder-arm separation angle at the maximum backswing and left foot touchdown, throwing-arm elevation angles at left foot takeoff, right foot takeoff, and left foot touchdown, hipshoulder separation at the left foot touchdown, and trunk tilt angle at the left foot touchdown had significant effects on the gain in discus speed during the delivery phase for the elite male and female discus throwers. Throwing-arm elevation angles at the maximum back swing and right foot takeoff, and hip-shoulder and shoulder-arm separation angles at right foot takeoff also had significant effects on the gain in discus speed during the delivery phase for the elite male discus throwers. Further, the shoulder-arm separation angle at the left foot takeoff had significant effect on the gain of discus speed during the delivery phase for the elite female discus throwers. Discus speed at the left foot touchdown was negatively correlated to the gain in the discus speed during the delivery phase. Discussion / Conclusions The results of this study suggest that the physical and technical training of the elite discus throwers should be focused on the ability to gain discus speed during the delivery phase. Discus throwers should control the discus speed before the delivery phase. The hip-shoulder separation angle and trunk tilt angle at the left foot touchdown are critical technical factors for the elite male discus throwers to gain discus speed during the delivery phase. Throwing-arm elevation angle at the right foot touchdown and trunk tilt angle at the left foot touchdown are critical technical factors for the elite female discus throwers to gain discus speed during the delivery phase. Future studies are needed for a further comprehensive understanding of the effects of technical factors on the performance of discus throwing.